1989
DOI: 10.2351/1.4745241
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Laser Melt/Particle Injection Processing

Abstract: Investigations into crack formation in particle injected surfaces and into microstructural evolution during cladding were some of the recent developments in laser melt/particle injection processing. Both surface modification techniques involved blowing powder particles into a melt pool formed by a laser beam. When the particulate materials were metal carbides composite surface layers were formed and the thermal stresses that developed during cooling of the carbide injected layer resulted in the formation of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Later, this average particle size was reduced to within the range 60-100 mm (Cooper and Slebodnick, 1989;Kloosterman et al, 1998;Kool et al, 1999;Pei et al, 2002). an alternative method is the preplacement of particles on the surface of the substrate alloy in the form of a slurry, where in general, the particles have a smaller average size, ~45-60 mm Pang et al, 2005).…”
Section: Laser Powder Alloyingmentioning
confidence: 97%
“…Later, this average particle size was reduced to within the range 60-100 mm (Cooper and Slebodnick, 1989;Kloosterman et al, 1998;Kool et al, 1999;Pei et al, 2002). an alternative method is the preplacement of particles on the surface of the substrate alloy in the form of a slurry, where in general, the particles have a smaller average size, ~45-60 mm Pang et al, 2005).…”
Section: Laser Powder Alloyingmentioning
confidence: 97%
“…Phase δ helps refine the grain size and impeding dislocation in the structure. Introduction of tungsten carbide (WC) grains with a diameter over 10 µm into the system [27,28] shows higher wear resistance and hardness of the material. It was reported that big carbide particles could not be distributed homogenously throughout the whole volume of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…This results in non uniform distribution of hardness. Metal–carbide systems are commonly deposited using two separate powder feeders with regulated feed ratios that could not provide the same carbide content in the whole volume [27,28]. Introduction of a small amount of TiC nanoparticles into Inconel [29,30,31] resulted in a modified microstructure of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This necessitates the overlapping of many melted tracks, with the additional problems due to preheating of the regions of the substrate where subsequent tracks are melted, as reported for laser processing. [20][21][22][23] Hu and Baker 22 defined 'preheat' as the heat developed from melting the initial track, which then diffused by conduction throughout the work piece. Previous laser studies described overlapping investigations based on a titanium alloy, initially involved laser nitriding 22 and subsequently laser alloying which incorporated SiC powder.…”
Section: Introductionmentioning
confidence: 99%